Review of Electronic Medical Records in Indonesia and its Developments Based on Legal Regulations in Indonesia and its Harmonization with Electronic Health Records (Manual for Developing Countries) - Tirsa Sharon Tilaar; Pan Lindawaty Suherman Sewu (PT Mattawang Mediatama Solution, 2023)
A medical record is a system that aims to track health and hospital visits. It can also be used to assist doctors and nurses in understanding medical history and to assist medical personnel in making decisions about treating patients. The method used in this research is the normative juridical research method. The specifics of this research is descriptive-analytical research, which is research that seeks to analyze legal issues and the legal system, in order to better understand them so that conclusions can be drawn. Medical records are part of the obligations of all doctors and dentists to carry out their medical practice. This is in accordance with